Does the working environment matter? The mediating influence of the working environment between compensation and employees' performance - Dr. Rafiullah,; Dr. Khalid Rehman (Corresponding Author),; Muhammad Kamran Khan,; Dr. Adnan Khank,; Dr. Ume Ruqia Saadat,; Furqan Ullah Khan, (Al-Qanṭara, 2023)
Purpose: The current research aimed to explore the mediating role of the working environment in the association between compensation and employee performance. The study established specific objectives, focusing first on assessing the impact of compensation on the performance of employees in the banking sector. The second objective was dedicated to investigating the mediating role of the working environment between compensation and employee performance within selected banks in Dera Ismail Khan. Design/Methodology/Approach: A total of 291 participants, drawn from a pool of 1045 employees in the banking sector within the Dera Ismail Khan region, were included in the study. Utilizing self-designed questionnaires, distributed and collected on-site, 281 responses were considered suitable for subsequent statistical analysis. Data analysis was conducted using SPSS version 26, employing both descriptive and inferential statistics aligned with the research objectives. Frequency tables, percentages, and means were computed to interpret the data substantively. Findings: Inferential statistics, specifically the Pearson correlation coefficient (r), were employed to ascertain the existence of a significant relationship between independent variables (compensation types: Extrinsic, intrinsic), the mediating variable (working environment), and the dependent variable (employee performance). The significance level for analysis and interpretation was set at 0.05. Research Limitations: The study, conducted in both public and private banks of Dera Ismail Khan from October 2023, revealed that both intrinsic and extrinsic components of compensation significantly impacted employee performance. Additionally, intrinsic and extrinsic rewards emerged as crucial predictors, with the working environment demonstrating a significant effect on employee performance. Practical Implications: Based on the findings, the researcher recommended initiatives such as increasing employee pay, promotions, and increments, maintaining cooperation among coworkers, ensuring timely promotions, and fostering a cooperative working environment. These recommendations aim to enhance organizational performance by positively influencing employee satisfaction and performance.